Feasibility cluster randomised controlled trial of a within-consultation intervention to reduce antibiotic prescribing for children presenting to primary care with acute respiratory tract infection and cough. Issue 5 (9th May 2017) - Blair, Peter S; Turnbull, Sophie; Ingram, Jenny; Redmond, Niamh; Lucas, Patricia Jane; Cabral, Christie; Hollinghurst, Sandra; Dixon, Padraig; Peters, Tim J; Horwood, Jeremy; Little, Paul; Francis, Nick A; et al.
Abstract : Objective: To investigate recruitment and retention, data collection methods and the acceptability of a 'within-consultation' complex intervention designed to reduce antibiotic prescribing. Design: Primary care feasibility cluster randomised controlled trial. Setting: 32 general practices in South West England recruiting children from October 2014 to April 2015. Participants: Children (aged 3 months to <12 years) with acute cough and respiratory tract infection (RTI). Intervention: A web-based clinician-focussed clinical rule to predict risk of future hospitalisation and a printed leaflet with individualised child health information for carers, safety-netting advice and a treatment decision record. Controls: Usual practice, with clinicians recording data on symptoms, signs and treatment decisions. Results: Of 542 children invited, 501 (92.4%) consented to participate, a month ahead of schedule. Antibiotic prescribing data were collected for all children, follow-up data for 495 (98.8%) and the National Health Service resource use data for 494 (98.6%). The overall antibiotic prescribing rates for children's RTIs were 25% and 15.8% (p=0.018) in intervention and control groups, respectively. We found evidence of postrandomisation differential recruitment: the number of children recruited to the intervention arm was higher (292 vs 209); over half were recruited by prescribing nurses compared with less than a third in the control arm; children in the intervention arm were younger (median age 2 vs 3 years controls, p=0.03) and appeared to be more unwell than those in the control arm with higher respiratory rates (p<0.0001), wheeze prevalence (p=0.007) and global illness severity scores assessed by carers (p=0.045) and clinicians (p=0.01). Interviews with clinicians confirmed preferential recruitment of less unwell children to the trial, more so in the control arm. Conclusion: Differential recruitment may explain the paradoxical antibiotic prescribing rates. Future cluster level studies should consider designs which remove the need for individual consent postrandomisation and embed the intervention within electronic primary care records. Trial registration number: ISRCTN 23547970 UKCRN study ID: 16891